2004
DOI: 10.1016/s0092-8674(04)00335-6
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Expansion of T Cells during Immune Insufficiency Generates Autoimmunity

Abstract: During illness and stress, the immune system can suffer a considerable loss of T cells (lymphopenia). The remaining T cells undergo vigorous compensatory expansion, known as homeostatic proliferation, to reconstitute the immune system. Interestingly, human diseases of autoimmune etiology often present with immune deficiencies such as lymphopenia. In this study, we show that reduced T cell numbers and the resulting exaggerated homeostatic-type proliferation of T cells generate autoimmunity. The cycling T cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
561
5
19

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 618 publications
(618 citation statements)
references
References 63 publications
33
561
5
19
Order By: Relevance
“…This T-cell expansion and acquisition of a memory phenotype is also associated with enhanced effector functions, determined by ex vivo analysis of interferon-γ (IFN-γ) release and cytolysis [12,14,15]. In a recent autoimmunity study, King et al showed that the inherent lymphopenia in non-obese diabetic (NOD) mice and increased expression of IL-21 drives the homeostatic expansion of autoreactive cells, precipitating self-tissue destruction [17]. Furthermore, adoptive transfer of naïve lymphocytic choriomenigitis virus (LCMV)-specific CD8 + T-cell receptor (TCR) transgenic splenocytes into LCMV-infected lymphodepleted, but not replete, hosts rapidly reduced viral titers to below detection limits [13].…”
Section: A Link Between Lymphodepletion and Augmented Immune Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…This T-cell expansion and acquisition of a memory phenotype is also associated with enhanced effector functions, determined by ex vivo analysis of interferon-γ (IFN-γ) release and cytolysis [12,14,15]. In a recent autoimmunity study, King et al showed that the inherent lymphopenia in non-obese diabetic (NOD) mice and increased expression of IL-21 drives the homeostatic expansion of autoreactive cells, precipitating self-tissue destruction [17]. Furthermore, adoptive transfer of naïve lymphocytic choriomenigitis virus (LCMV)-specific CD8 + T-cell receptor (TCR) transgenic splenocytes into LCMV-infected lymphodepleted, but not replete, hosts rapidly reduced viral titers to below detection limits [13].…”
Section: A Link Between Lymphodepletion and Augmented Immune Functionmentioning
confidence: 99%
“…It is also important to mention the newly discovered cytokine IL-21, which shares homology with IL-2 and IL-15 and binds their common γc receptor [44,45]. This cytokine might augment the function of adoptively transferred tumor-specific CD8 + T cells [17,46] and is the subject of ongoing investigations. Many unresolved questions regarding the use of γc receptor cytokines remain to be answered (Box 1).…”
Section: Evidence For the Presence Of Homeostatic Cellular Cytokine 'mentioning
confidence: 99%
“…Homeostatic expansion is known to depend on the availability of space in peripheral lymphoid organs (6,7). To determine whether inhibition of homeostatic T cell proliferation is able to prevent autoimmune arthritis, 3-week-old K/BxN mice were infused with CD4ϩ T cells purified from BxN mice.…”
Section: Resultsmentioning
confidence: 99%
“…This homeostatic proliferation of T cells may favor oligoclonal expansion of autoreactive T cells with phenotypes distinct from those of normal naive T cells, leading to an abnormally restricted peripheral T cell repertoire. This explanation of lymphopenia-provoked autoimmunity was recently substantiated in a model of autoimmune diabetes, the diabetic NOD mouse (7), but remains to be tested in the setting of RA.…”
mentioning
confidence: 91%
“…Similar observations were made using both IL-21 and IL-21R genetically deficient mice. In addition, a critical role for IL-21 in the expansion of inflammatory Tcells was shown to play a pivotal role in chronic inflammatory diseases such as encephalomyelitis, arthritis and diabetes [10][11][12].…”
mentioning
confidence: 99%